Save a Child: How to Identify and Report Child Abuse - Andrew E. Toelle; Kate Fogarty (EDIS)
People who work with children, parents, and the general public may at some point in their lives and careers have to report child abuse. It is important that you be able to recognize the symptoms of abuse and be able to contact the appropriate authorities. By reporting abuse, you may save a child’s life or prevent serious injury. This 4-page fact sheet discusses child abuse laws and procedures for reporting abuse. It also contains information about different types of abuse and how to identify abused or neglected children. Characteristics listed here are general and intended as guidelines. A child or family may exhibit many warning signs of abuse, though no abuse has occurred or ever will occur. Written by Andrew E. Toelle and Kate Fogarty and published by the UF Department of Family Youth and Community Sciences, January 2013.